High-resolution RNA 3′-ends mapping of bacterial Rho-dependent transcripts. Issue 13 (14th April 2018) - Dar, Daniel; Sorek, Rotem
Abstract: Transcription termination in bacteria can occur either via Rho-dependent or independent (intrinsic) mechanisms. Intrinsic terminators are composed of a stem-loop RNA structure followed by a uridine stretch and are known to terminate in a precise manner. In contrast, Rho-dependent terminators have more loosely defined characteristics and are thought to terminate in a diffuse manner. While transcripts ending in an intrinsic terminator are protected from 3′-5′ exonuclease digestion due to the stem-loop structure of the terminator, it remains unclear what protects Rho-dependent transcripts from being degraded. In this study, we mapped the exact steady-state RNA 3′ ends of hundreds of Escherichia coli genes terminated either by Rho-dependent or independent mechanisms. We found that transcripts generated from Rho-dependent termination have precise 3′-ends at steady state. These termini were localized immediately downstream of energetically stable stem-loop structures, which were not followed by uridine rich sequences. We provide evidence that these structures protect Rho-dependent transcripts from 3′-5′ exonucleases such as PNPase and RNase II, and present data localizing the Rho-utilization ( rut ) sites immediately downstream of these protective structures. This study represents the first extensive in-vivo map of exact RNA 3′-ends of Rho-dependent transcripts in E. coli .